Development of the Nganjuk Regency Legal Documentation and Information Network (JDIH) Based on Co-Creation within the New Public Governance Paradigm - Mariyanti, Dwi; Wardiyanto, Bintoro (Reflection Journal, 2026)
The digital transformation of government and strengthening public information disclosure policies have encouraged local governments to develop legal information services that are transparent, participatory and responsive. However, nationally, the achievement of information openness still faces challenges, as reflected in the 2025 Public Information Openness Index (IKIP) value of 66.43, down 9.22 points compared to 2024 of 75.65. This condition shows that information disclosure, especially legal information services at the regional level, has not been effectively institutionalized. One of the instruments used is the Legal Documentation and Information Network (JDIH), although its management is still administrative and focuses on providing legal documents. This research aims to analyze the development of JDIH Nganjuk Regency based on co-creation within the New Public Governance (NPG) framework. A qualitative approach was used with a case study design through in-depth interviews, observations and documentation studies which were analyzed thematically and interpretively. The research results show that although JDIH Nganjuk Regency has run well administratively and received institutional recognition, management is still government centric and has not provided meaningful participation space for the community. The main principles of NPG, especially governance networks and co-creation, have not been systematically institutionalized due to institutional limitations, low public legal literacy, and the unavailability of clear participation mechanisms. The conclusion of this research confirms that the development of JDIH based on co-creation in the NPG paradigm is a strategic need in improving legal information services and strengthening the legitimacy of regional policies, which requires support by strengthening governance networks, increasing management capacity, and sustainable participatory development